QUALITY ASSESSMENT OF MULTIFOCAL DIFFRACTIVE LENS IMAGES - V. G. Kolobrodov; G. S. Timchik; Ie. A. Siryi (Приборы и методы измерений, 2015)
The method of trifocal diffractive lens images quality assessment in the presence of the background illumination is proposed. The background component with nonuniform intensity distribution is modeled. The effect of diffractive lens light efficiency and spherical aberration on the image contrast is presented.